The Relationship Between Metabolic Circumstance and Epigenetic Acetylation in Myoblast Fate and Function - Lim, Sean (Université d'Ottawa / University of Ottawa, 2021)
Muscle tissue is grown and maintained by muscle stem cells termed satellite cells. Activated satellite cells become myoblasts, which must proliferate then differentiate into functional muscle. This process, known as myogenesis, is controlled by a cascade of epigenetic regulatory events. One facet of this regulation is histone acetylation, which can be influenced by the availability of metabolites within a cell. In this study, the ability of glucose, pyruvate, or glutamine to change histone acetylation levels in cultured myoblasts was investigated. Changing concentrations of glucose or pyruvate had no effect but decreasing the availability of glutamine in cell culture from 2mM to 0.2mM resulted in proliferating myoblasts accruing a hyperacetylated histone phenotype. However, when the same concentration of glutamine was used on differentiating myoblasts the hyperacetylated phenotype was lost and no change to differentiation was observed. This study demonstrates the potentials and limitations of altering epigenetic acetylation with metabolic circumstance. -- Le développement du tissu musculaire est soutenu par les cellules souches musculaires, communément appelées cellules satellites. Les cellules satellites activées se transforment en myoblastes qui doivent ensuite proliférer et se différencier en muscle fonctionnel. Ce processus, connu comme myogenèse, est contrôlé par une cascade de régulation épigénétique. Un aspect de ce processus est l’acétylation d’histones, qui peut être influencée par la disponibilité de métabolites dans la cellule. Dans cette étude de cas, la capacité du glucose, pyruvate, ou glutamine à changer les niveaux d’acétylation d’histones a été examinée. Le changement des concentrations de glucose ou de pyruvate n’a généré aucun effet, mais la diminution de la disponibilité de la glutamine dans la culture cellulaire de 2mM à 0.2mM a eu pour résultat une prolifération de myoblastes présentant un phénotype d’histones hyper-acétylées. Pourtant, quand la même concentration de glutamine a été utilisée pour différencier les myoblastes, le phénotype hyper-acétylé n’a pas été observé et aucun changement de différenciation n’a pu être détecté. Cette étude démontre le potentiel et les limites des modifications de l’acétylation épigénétique selon les circonstances métaboliques.
Keywords: Myoblasts; Epigenetic; Histone; Metabolism